Challenges in the care of patients with Chagas disease in the Brazilian public health system: A qualitative study with primary health care doctors - Damasceno, Renata Fiúza; Sabino, Ester Cerdeira; Ferreira, Ariela Mota; Ribeiro, Antonio Luiz Pinho; Moreira, Hugo Fonseca; Prates, Thalita Emily Cezário; Sampaio, Cristina Andrade; Haikal, Desirée Sant´Ana (PLOS Neglected Tropical Diseases, 2020)
Author summary Chagas disease (CD) is a parasitic disease caused by Trypanosoma cruzi which predominantly affects poor and vulnerable populations. In the Brazilian public health system, the expansion of Primary Health Care (PHC) services to remote and disadvantaged areas has facilitated the access of patients with CD to medical care. However, preliminary results from a cohort study that followed almost two thousand CD patients in an endemic region in Brazil showed that 74% of these patients were not followed by a doctor or were followed irregularly. Our study explored the challenges of family doctors to provide care to patients with CD in a municipality in that region through a qualitative approach. We conducted a focus group with 15 family doctors. The family doctors pointed out the following challenges for care to CD patients in PHC: unsatisfactory medical training; uncertainties regarding antiparasitic treatment in the chronic phase of the disease; difficulty in patient access to specialized care when necessary; and trivialization of the disease by patients as a barrier to seeking care. The results of this study may contribute to the development of strategies to improve the clinical management of CD in PHC.